2023
DOI: 10.1039/d3tc01160g
|View full text |Cite
|
Sign up to set email alerts
|

Promising novel thermoelectric materials: two-dimensional penta-like PtPX (X = S, Se, Te) nanosheets

Abstract: Exploring high-power self-charging technologies is essential given the quick development of wearable and implantable devices. Devices that convert body heat into electricity and are based on flexible materials are known...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…The DP constant E 1 describes the variation of the band edges (VBM and CBM) with uniaxial strain and is determined by E 1 = E edge /∂(Δ a / a 0 ), where E edge is the band edge shift. Based on the parabolic fit of the band structure at the VBM and CBM, we estimated the carrier effective mass by using the formula m * = ℏ 2 /(∂ 2 E ( k )/∂ k 2 ), where E ( k ) represents the Kohn–Sham eigenenergy with the wave vector k . , The carrier mobility μ can be obtained as a relation to the relaxation time μ = τ e m * . Table lists the calculated results for all the above-mentioned parameters of the BiOClBr, BiOClI, and BiOBrI monolayers at 300 K. It is evident that the m * of the hole is greater than that of the electron for all three monolayers, consistent with the different features between the VBM and CBM mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…The DP constant E 1 describes the variation of the band edges (VBM and CBM) with uniaxial strain and is determined by E 1 = E edge /∂(Δ a / a 0 ), where E edge is the band edge shift. Based on the parabolic fit of the band structure at the VBM and CBM, we estimated the carrier effective mass by using the formula m * = ℏ 2 /(∂ 2 E ( k )/∂ k 2 ), where E ( k ) represents the Kohn–Sham eigenenergy with the wave vector k . , The carrier mobility μ can be obtained as a relation to the relaxation time μ = τ e m * . Table lists the calculated results for all the above-mentioned parameters of the BiOClBr, BiOClI, and BiOBrI monolayers at 300 K. It is evident that the m * of the hole is greater than that of the electron for all three monolayers, consistent with the different features between the VBM and CBM mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…25 Recent studies have shown that the PdPSe monolayer has a moderate theoretical carrier mobility of 21.37 cm 2 V −1 s −1 and a high on/off ratio of about 10 8 , which makes it suitable for FET device applications. 26 Our previous study reported the excellent electronic and interfacial properties of a vdW heterojunction composed of SnS and TaS 2 monolayers. 27 Therefore, development of new 2D vdW heterojunctions based on novel 2D materials is scientifically desirable to make environmentally friendly and energy efficient optoelectronic applications.…”
Section: Introductionmentioning
confidence: 95%
“…The major factor that can suppress κ l in a crystal is lattice anharmonicity, which can be triggered by introducing weak-bonding elements, stereochemically active lone-pair electrons, 6 rattling atoms, 6 bonding heterogeneity in the crystal, i.e. , the presence of stronger bonds along with weaker anharmonic bonds, 6–11 etc. Recently, Li et al have shown that the introduction of Ba or Sr atoms into the SnS 2 framework weakens the chemical bonds and enhances the lattice anharmonicity, which leads to a reduction of κ l values of 0.15 and 0.17 W m −1 K −1 at 900 K for BaSnS 3 and SrSnS 3 , respectively.…”
Section: Introductionmentioning
confidence: 99%